Estimation of the stress–strength reliability using lower record ranked set sampling scheme under the generalized exponential distribution. Issue 1 (2nd January 2020) - Sadeghpour, Amineh; Salehi, Mahdi; Nezakati, Ahmad
ABSTRACT: This paper presents likelihood and Bayesian estimation of stress–strength reliability parameter (say R ) based on lower record ranked set sampling scheme from the generalized exponential distribution. Maximum likelihood, uniformly minimum variance unbiased as well as the Bayesian estimators of R are derived and their properties are studied. Constructing and comparing various confidence intervals for the parameter R is also examined. Finally, the rocket-motor experiment data is analysed for illustrating purposes.